PANI-Co3O4 with excellent specific capacitance as an electrode for supercapacitors. Issue 6 (15th March 2021) - Fan, Yanyun; Chen, Hongmei; Li, Yuankai; Cui, Danfeng; Fan, Zheng; Xue, Chenyang
Abstract: In this work, a novel PANI-Co3 O4 supercapacitor electrode used foamed nickel as substrate was synthesized by hydrothermal and in situ polymerized method. The PANI-Co3 O4 was visualized by XRD, SEM, TEM and XPS, and its morphology showed that the Co3 O4 nanorods were coated in PANI more uniformly. Electrochemical studies revealed that the specific capacitance of PANI-Co3 O4 composite at 1 A g −1 is 3105.46 F g −1 (31.05 F cm −2 ), which is 14.7 times higher than that of Co3 O4 alone. Additionally, the electric capacity maintained 74.81% of the original value after 3000 cycles, indicating satisfactory cycle stability. Moreover, the PANI-Co3 O4 //AC showed a high energy density of 58.84 W h kg −1 at 0.16 kW kg −1 . This study not only points out the new way of PANI/semiconductor metal oxide composite, but also has a great potential for application in high-performance energy storage devices.